1982
DOI: 10.2307/3898265
|View full text |Cite
|
Sign up to set email alerts
|

Production and Nutritive Value of Aspen Understory, Black Hills

Abstract: duction of and nutrient concentrationsin understory vegetation was measured in aspen stands representing three different seral stages in the Black Hills. There was little variation in concentrations of nutritive elements in the same plant species among stands. Differences in species composition and shrub, forb, grass, and total production caused some variation in total available nutrients. Production of aspen understory, while variable (676-1226 kg/ha), was one of the higher producing types in the area. Digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…Bur oak (Quercus macrocarpa), hop-hornbeam (Ostrya virginiana), and green ash (Fraxinus pennsylvanica) also occupied the BHNF, comprising < 10% Alexander 1987, Froiland 1990). Common shrubs included western snowberry (Symphoricarpos occidentalis), white coralberry (S. albus), kinnikinnick (Arctostaphylos uvaursi), and common juniper (Juniperus comunis) (Severson andThilenius 1976, Hoffman and.…”
Section: Study Areamentioning
confidence: 99%
“…Bur oak (Quercus macrocarpa), hop-hornbeam (Ostrya virginiana), and green ash (Fraxinus pennsylvanica) also occupied the BHNF, comprising < 10% Alexander 1987, Froiland 1990). Common shrubs included western snowberry (Symphoricarpos occidentalis), white coralberry (S. albus), kinnikinnick (Arctostaphylos uvaursi), and common juniper (Juniperus comunis) (Severson andThilenius 1976, Hoffman and.…”
Section: Study Areamentioning
confidence: 99%
“…Reynolds (1969) found that an aspen stand produced 6 times the understory of a mixed conifer stand in Arizona. Severson (1982) noted that only moist, grass-dominated meadows produced more forage than did unmanaged aspen stands in the Black Hills. Aspen stands also contain more species in the understory than do ponderosa pine stands.…”
Section: Montane Conifer Forest (Mixed Conifer Series) Rocky Mountainmentioning
confidence: 99%
“…Our data also implied that dense sapling stands had a slight negative influence on ruffed grouse occupancy. In Minnesota and Wisconsin, investigators found younger age classes (< 25 yr) of forest were preferred over mature stands , Gullion 1989, Severson 1982. However, the young age classes evaluated in those studies consisted primarily of aspen.…”
Section: Discussionmentioning
confidence: 98%
“…Bur oak (Quercus macrocarpa), hop-hornbeam (Ostrya virginiana), and green ash (Fraxinus pennsylvanica) also occupied the BHNF, comprising < 10% Alexander 1987, Froiland 1990). (Severson andThilenius 1976, Hoffman and.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation